Managing village fund direct cash assistance during the COVID-19 pandemic: Local governance and community resilience in Cikalong Village, Indonesia - Lina Marliani; Ginanjar Wira Saputra; Dede Syahril Sidik; Ally Mom (Interdisciplinary International Journal of Conservation and Culture, 2023)
The COVID-19 pandemic compelled Indonesian villages to reallocate Village Funds from routine development toward emergency social protection, including Village Fund Direct Cash Assistance (Bantuan Langsung Tunai Dana Desa/BLT-Desa). This study examines how BLT-Desa was managed in Cikalong Village, Cikalongwetan District, West Bandung Regency, with particular attention to planning, implementation, administration, reporting, and accountability. A descriptive qualitative case-study design was used. Data were derived from observation, documentary records, and interviews with seven informants comprising the village head, village secretary, village treasurer, and four community beneficiaries. Data were analyzed through reduction, display, and conclusion drawing, with source and technique triangulation. The findings show that the village government adapted quickly by reallocating the 2020 Village Fund and channeling a substantial share to emergency cash transfers. Technically, fund administration and distribution were generally implemented, but governance quality remained uneven. Transparency relied heavily on static information media, community participation in monitoring was limited, and reporting was sometimes delayed by weak staff discipline. The source records also reveal beneficiary-data inconsistencies that underline the importance of integrated social assistance databases. The study concludes that crisis-responsive fiscal flexibility must be accompanied by digital transparency, participatory oversight, reconciled beneficiary data, and stronger administrative accountability to transform short-term relief into durable village resilience.